Molecularly imprinted biomimetic plasmonic sensor decorated with gold nanoparticles for selective and sensitive detection of bisphenol A - Ilgım Göktürk; Süleyman Aşır; Deniz Türkmen; Adil Denizli; Fatma Yılmaz (Talanta Open)
Molecularly imprinted polymers inspired by antigen-antibody interactions have received substantial interest as a biomimetic artificial receptor system in environmental applications. Herein, we present a molecularly imprinted surface plasmon resonance sensor integrated with gold nanoparticles for the identification of bisphenol A (BPA), an endocrine-disrupting chemical. We synthesized BPA-imprinted nanofilm consisting of amino acid-based functional monomers to selectively detect BPA from synthetic wastewater samples. BPA-spiked synthetic wastewater samples were analyzed to ensure the method's reliability and feasibility. Under ideal conditions, the suggested approach performed well in terms of analytical performance to bisphenol A, with a wide linear range of 0.1 to 10 µg/L and LOD of 10 ng/L. The sensor results align well with the Langmuir adsorption model. It has also been shown that repeated use of the sensor can be achieved. According to selectivity studies, bisphenol A adsorbed within the imprinted cavities favorably compared to 4-nitrophenol and phenol. The produced bisphenol A-imprinted surface plasmon resonance sensor provides improved sensitivity based on the signal amplification strategy, unconjugated sensing without the need for labelling, real-time sensing, low sample consumption rates, quantifiable assessment, and outstanding kinetic rate constant calculation in actual samples. Also, because the produced sensor is reusable with relative standard deviations (RSD)<1.25, indicating the sensor's precision, the surface plasmon resonance-based biomimetic BPA sensor is simple to practice and a cost-effective option.